Neonatal sepsis - Angelica Dessì; Chiara Pravettoni; Giovanni Ottonello; Francesca Birocchi; Francesca Cioglia; Vassilios Fanos (Hygeia Press di Corridori Marinella, 2014)
In this paper on neonatal sepsis, after a short presentation of etiopathogenesis and physiopathology, we will briefly present the clinical picture, the diagnosis and the therapy. Concerning diagnosis, we will focus our attention on procalcitonin (PCT), serum amyloid A (SAA), presepsin (sCD14) and metabolomics. Three practical tables complete the review.   Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken